جهود الشيخ محمد أبو زهرة في الدعوة إلى الله - لبزة, سامية; عوينات, مسعودة; هبيته, منال (جامعة الوادي university of eloued, 2015)
- لقد تناول بحثنا أهم مراحل حياة الشيخ محمد أبو زهرة ومجهوداته الدعوية، من مولده ونشأته وطلبه للعلم إلى جهوده. وقد خاض الشيخ معارك كثيرة للدفاع عن الدعوة والشريعة الإسلامية، واعتمد في دعوة على عدة وسائل منها: إلقاء المحاضرات، معالجة القضايا، تأليف الكتب، كتابة المقالات، حضور المؤتمرات، الإفتاء. وقد كان رمزا للجهاد وحب الوطن. Research Summary: - We've dealt with the most important stages of the life of Sheikh Muhammad Abu Zahra and his efforts preaching, from his birth and upbringing and his application of science to his efforts. Sheikh has fought many battles to defend the call and Islamic law, was adopted at the invitation of several ways, including: lecturing, addressing the issues, writing books, writing articles, attending conferences, the advisory. It was a symbol of Jihad and patriotism.
دعوة